A Pilot Study on the Anti-Inflammatory Effects of Tacrolimus in Ankylosing Spondylitis: Evidence from Human Samples and a Murine Model - Park, Sooin; Kim, Moon-Ju; Lee, Yu Jeong; Yu, Sung Min; Lee, Hae-in; Jin, So-Hee; Choi, A-ra; Shim, Seung Cheol; Won, Eun Jeong; Kim, Tae-Jong (Archives of Rheumatology, 2025)
Background/Aims: Evaluate anti-inflammatory and therapeutic effects of tacrolimus in ankylosing spondylitis (AS). Materials and Methods: PBMCs and SFMCs from AS patients treated with tacrolimus; flow cytometry measured IFN-γ, IL-17A, GM-CSF. Cytokines (IFN-γ, IL-17A, TNF-α, GM-CSF) in PBMC supernatants by ELISA. In vivo AS mouse model: clinical arthritis scores and flow cytometry for IFN-γ, IL-17A, TNF-α. Results: Tacrolimus suppressed cytokine production in patient PBMCs/SFMCs. In mice, tacrolimus reduced arthritis scores and cytokine-producing cells. Conclusion: Tacrolimus shows potential as AS therapy by suppressing inflammatory cytokines ex vivo and in vivo models.